1997
DOI: 10.1046/j.1365-2958.1997.4991867.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a maintenance system on rolling circle replicating plasmid pVT736‐1

Abstract: SummaryDistribution of plasmid molecules to the two daughter cells at cell division is of major importance for their stable inheritance. Several mechanisms that control equipartitioning of low-copy-number plasmids have been described in molecular terms. However, no homologous or analogous systems have been identified for intermediate or high-copy-number plasmids, including rolling circle replicating (RCR) plasmids. It has been suggested that distribution of such plasmids at cell division relies solely on rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…(1989). DNA–DNA hybridization conditions, and transformation by electroporation have been described previously (Galli and LeBlanc, 1997). Standard three‐step PCR experiments were performed with Taq polymerase from Promega (Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…(1989). DNA–DNA hybridization conditions, and transformation by electroporation have been described previously (Galli and LeBlanc, 1997). Standard three‐step PCR experiments were performed with Taq polymerase from Promega (Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Standard recombinant DNA techniques were performed as described by Sambrook et al (47). DNA-DNA hybridization conditions and transformation by electroporation were as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has focused mainly on the characterization of pVT736-1, one of the first rolling circle replicating (RCR) plasmids isolated from gram-negative bacteria (17,18). It was shown that pVT736-1 was cryptic, that it was not related to RCR plasmids found in gram-positive bacteria, and that it encoded a new type of partitioning system (20).…”
mentioning
confidence: 99%
“…Plasmid DNA was isolated from A. actinomycetemcomitans and E. coli as described previously (11). Restriction endonucleases, Klenow polymerase I, and T4 DNA ligase were used in accordance with the manufacturer's instructions (Gibco-BRL).…”
Section: Methodsmentioning
confidence: 99%
“…Standard re-combinant DNA techniques were performed as described by Sambrook et al (23). DNA-DNA hybridization conditions and transformation by electroporation have been described previously (11). Standard three-step PCR experiments were performed with Taq polymerase from Promega (Madison, Wis.).…”
Section: Methodsmentioning
confidence: 99%